Self, Soul and Body in Religious Experience - Baumgarten, Albert I.; Assmann, Jan.; Stroumsa, Guy G. (Numen Book Series, 1998)
The papers in this volume were delivered at the first international colloquium by the Jacob Taubes Minerva Center for Religious Anthropology at Bar Ilan University, held in February 1995. Concepts of Self, Soul and Body are so close to the physiological layers of life that we may imagine them to be biological as well; but in fact, they are social constructs, and a source of fundamental metaphors for the classification of experience. They thus help organize the world, at the same time as they express basic human identity. They vary from culture to culture and can productively be compared and contrasted from one setting to another. We intend these papers to be a test case of the benefit to be gained from attention to Religious Anthropology.